Deploying perioperative nurses during the COVID-19 pandemic - Clayton, Patrice; Mendez, Sonia; Patel, Komal (Operating Room Nurses Association of Canada Journal, 2024)
Educators in the hospital setting collaborated in the development of pandemic training sessions during the global outbreak of COVID-19. The outbreak created unique challenges at all levels of healthcare including nursing. Within the surgical program of a tertiary hospital, elective surgical procedures were halted and the perioperative departments (PACU, Endoscopy, and Day Surgery) were converted into small medical units and a critical care unit. Clinical nurse educators planned education sessions that promoted an allhands- on-deck approach, to provide effective and efficient learning opportunities for redeployed perioperative nursing staff. Delivery of educational sessions were organized through self-learning modules, in-class learning, and simulation format. The purpose of this paper is to discuss and share the process used, in one acute care hospital, for the deployment of perioperative nurses to medical units and the level of education required for perioperative nurses, with varying skill levels, to be deployed effectively.